Competitive advantages in the market of consulting services: marketing aspect - Yevtushenko, Natalia; Fedorchenko, Andriy (Business: Theory and Practice, 2023)
The article summarizes the arguments and counterarguments about the features of the formation of competitive advantages in the Ukrainian market of services on the example of consulting for the period 2010–2021. According to the results of the analysis and generalization, the author’s understanding of the concept of “competitive advantages”, the factors of their formation presented. The article describes the interconnection of competitive strategies with the process of forming competitive advantages. The process of economic analysis revealed the immaturity of the consulting market in Ukraine and its institutional vulnerability. The reasons for the instability of demand for consulting services described. The leadership matrix for Ukrainian consulting companies built in accordance with the typology of competitive strategies F. Kotler. The analysis revealed an updated list of competitive advantages of companies that formed under the influence of the Covid-19 pandemic and martial law in Ukraine. It proved that the main advantage of companies is the competence of consultants. Recommendations for the development of consulting companies in Ukraine and strengthening their competitive advantages, taking into account the construction of an effective marketing management system and use the consulting service standard. The research results can be useful for consulting companies wishing to improve their competitiveness and to expand the segment of their services in the market.